Ethnoveterinary Practices of Medicinal Plants Among Tribes of Tribal District of North Waziristan, Khyber Pakhtunkhwa, Pakistan - Rehman, Sabith; Iqbal, Zafar; Qureshi, Rahmatullah; Rahman, Inayat Ur; Sakhi, Shazia; Khan, Imran; Hashem, Abeer; Al-Arjani, Al-Bandari Fahad; Almutairi, Khalid F.; Abd_Allah, Elsayed Fathi; Ali, Niaz; Khan, Muhammad Azhar; et al. (Frontiers in Veterinary Science, 2022)
Domestic animals play a vital role in the development of human civilization. Plants are utilized as remedies for a variety of domestic animals, in addition to humans. The tribes of North Waziristan are extremely familiar with the therapeutic potential of medicinal plants as ethnoveterinary medicines. The present study was carried out during 2018–2019 to record ethno-veterinary knowledge of the local plants that are being used by the tribal communities of North Waziristan, Khyber Pakhtunkhwa, Pakistan. In all, 56 medicinal plant species belonging to 42 families are identified, which are reported to treat 45 different animal diseases. These included 32 herbs, 12 shrubs, and 12 trees. Among the plant families, Asteraceae contributed the most species (5 spp.), followed by Amaranthaceae (4 spp.), Solanaceae (4 species), and Alliaceae, Araceae, and Lamiaceae (02 spp. each). The most common ethnoveterinary applications were documented for the treatment of blood in urine, bone injury, colic, indigestion, postpartum retention, skin diseases, constipation, increased milk production, mastitis, foot, and mouth diseases.